Applications of an Innovative Strength Parameter Estimation Method of the SoilRock Mixture in Evaluating the Deposit Slope Stability Under Rainfall - Fu, Xiaodong; Zhang, Zhenping; Sheng, Qian; Zhou, Yongqiang; Huang, Juehao; Wu, Zhe; Liu, Mingyang (Frontiers in Earth Science, 2021)
Deposit landslides are one of the most representative geological hazards around the world, and the poor understanding of the mechanical characteristics of the soilrock mixture (S-RM) increases the difficulties in evaluating the stability of the deposit slope subjected to rainfall. This study attempted to propose an innovative strength parameter estimation method of the S-RM based on the concept and format of the generalized HoekBrown criterion. The system of “rock blocks–soil–contact surface” was considered the main source providing resistance to the external force, and the effect of the soil matrix, rock blocks, and the contact surface between them was taken into account. The verification of the estimation method was proved based on the abundant test data. A typical deposit slope located in the Taoyuan region of Yunnan Province, China, was selected as a case study, and the estimation method was applied to provide the shear parameters of the S-RM. The slope stability subjected to different types of rainfall was analyzed considering the parameter deteriorations, and the results show that the deposit landslide is more prone to the wave-type rainfall, which shows a deeper response depth of pore water pressure and a smaller safety factor. The present study suggests a simple estimation method for the shear parameters of the S-RM using a few parameters for the engineers and provides an understanding of the deposit slope stability during the rainfall process.